El Aprendizaje Basado en Juegos (ABJ) y las relaciones lógico-matemáticas en niños de 4 a 5 años de la Escuela de Educación Básica José Ingenieros de la ciudad de Loja, periodo 2022-2023. - Atarama Mora, Cristin Aytana (2024)
Logical-mathematical relationships refer to the development of mathematical thinking in children from an early age, allowing them to understand the environment around them through the formation of notions such as seriation, grouping, comparison, space, time, number, colors and figures, which are important to contribute to their progress, allowing them to form solid bases to generate more knowledge, not only in the area of mathematics, but in any educational aspect and in their daily lives. Thus, the present research work seeks to determine how game-based learning (GBL) strengthens logical-mathematical relationships in children from 4 to 5 years of age at Escuela de Educación Básica José Ingenieros in the city of Loja, in the period 2022-2023. This research was carried out with a quasi-experimental design with a mixed approach, using inductive-deductive methods to give sense and order to the work and analytical-synthetic methods that allowed an individual analysis of the variables. This work was developed with a sample of twenty-seven children, to whom the Test de Competencias Matemática Básica - 3 (Topic-3) was applied, showing that in the pre-test 41% and 36% of the children are at a low level in counting, primary and secondary colors, geometric figures, notions of space, time and length, considering these results, an activity guide called “Conociendo el gran universo de las matemáticas” was elaborated and executed, to reinforce learning, achieving in the post-test a decrease in the difficulties found in children to 5% and 23% in the low level, thus showing that learning based on games (ABJ), allows children to reinforce logical-mathematical relationships based on fun activities that capture their attention, improving their knowledge. Keyword: ABJ, games, mathematics, notions, number, geometric figures, activities.